The Correlation between Students Vocabulary Master and Their Ability in Comprehending News Item at The Second Semester of Eleventh Class at SMA Negeri 1 Tanjung Bintang Lampung Selatan - Nurchurifiani, Eva (Lentera: Jurnal Ilmiah Kependidikan, 2015)
The purpose of teaching and learning English as foreign language is to enable the students to communicate in English both in readers forms in real communication and understand the foreign culture. There are skill that should be learnt by the student, they are listening, reading, writing and speaking. The students of the eleventh class should be able to master vocabulary and comprehend news item. In achieving the goal of curriculum, there are many students find difficult. They also make errors when they comprehend news item. It means that vocabulary is very important for the students to learn English. The objective of this research is to know and describe the studentsâ vocabulary mastery and their ability in comprehending news item and to know describe the correlation between studentsâ vocabulary mastery and their ability in comprehending news item. In taking the sample of the research, the writer used stratified proportional random sampling technique because the studentâs ability was heterogeneous. The population of the research is all the first semester in the eleventh class at SMAN 1 Tanjung Bintang Lampung Selatan. The writer took one class from seven classes and the class consisted of 37 class students. In collecting the data, the writer used objective test that were multiple choice, consisted of 50 items. In this research, product moment formula was used to analyze the data of the research. Based on the result of the research showed rcount = 0.670 is higher than rtable = 0.630 by n =37, there was correlation between vocabulary mastery and comprehending news item.  < (1-a) (k-3), n=37 there was significant correlation.